PENINGKATAN KOMPETENSI WIRAUSAHA MUDA MELALUI PROGRAM KEGIATAN KEWIRAUSAHAAN PADA BADAN USAHA AMAL NASYIATUL AISYIYAH KABUPATEN KENDAL - Dyah Pikanthi Diwanti; Suryanto Suryanto; Sri Iswati; Tri Siwi Agustina; Hari Basuki Notobroto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Nasyiatul Aisyiyah Kabupaten Kendal is one of the young women organizations of Muhammadiyah that has a business unit called Amal business entity Nasyiatul Aisyiyah (BUANA) which moves as a form of entrepreneurship organization. This series of activities began with the planning of events, implementation activities and evaluation, and a follow-up plan (RTL) in the form of creating an entrepreneurial database to see a few entrepreneurial competencies owned by entrepreneurship. The activities carried out by involving the elements of the leadership of branch leaders and leaders in the branches in the district of Kendal to be able to creatively and effectively apply the training results sustainably. The entrepreneurship Program successfully showed progress. The participant Database shows a success indicator where the majority of participants aged 37 – 45 are 39.8% of the total participants in this activity as much as 93 people. That means it is the productive age of existing entrepreneurs who strengthens the movement of BUANA. And the length of 1-10 years is the identification of participants from the beginning to contribute creative ideas in the development of BUANA. Competency has a strong influence on entrepreneurship (BUANA). It means that the need for HR competence becomes significant in contributing to the entrepreneurship of the Nasyiah organization in this case, BUANA (charity agency Nasyiatul Aisyiyah) Kabupaten Kendal.